2018
DOI: 10.1155/2018/9123912
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Consequences of Nonclosure of Mesenteric Defects after Traditional Right Colectomy

Abstract: Background There are still discrepancies among general/colorectal surgeons regarding closure of mesenteric defect in scientific literature. This study aimed to assess the long-term consequences of nonclosure of the mesenteric defect after open right colectomy. Methods A 7-year retrospectively collected and continuous database revealed 212 consecutive patients who had undergone traditional right colectomy without closing the mesenteric defects at Kaohsiung Chung-Gung Memorial Hospital; all patients were operate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A retrospective study of 195 patients showed that no patients had intestinal obstruction due to patent mesenteric defect after right hemicolectomy. Routine suture of mesenteric defect after operation may not bene t patients (8). A study of 530 patients showed that mesenteric defects caused complications in 4 cases (0.8%), of which 2 cases had intra-abdominal hernias causing small bowel obstruction, and 2 cases caused anastomotic torsion due to defects, but the overall study data cannot support that is beni cial for patients to close mesenteric defect (16).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A retrospective study of 195 patients showed that no patients had intestinal obstruction due to patent mesenteric defect after right hemicolectomy. Routine suture of mesenteric defect after operation may not bene t patients (8). A study of 530 patients showed that mesenteric defects caused complications in 4 cases (0.8%), of which 2 cases had intra-abdominal hernias causing small bowel obstruction, and 2 cases caused anastomotic torsion due to defects, but the overall study data cannot support that is beni cial for patients to close mesenteric defect (16).…”
Section: Discussionmentioning
confidence: 94%
“…Compared with traditional surgery, laparoscopic colon surgery has the advantages of less pain, small incision, rapid recovery, and short fasting time, and the effect of tumor treatment is equivalent to traditional surgery (3)(4)(5). However, there is controversy about whether to close the mesenteric defects after laparoscopic radical resection of colon cancer (6)(7)(8). The unclosed mesenteric defects after radical resection of right colon cancer may lead to complications such as hernia, volvulus, and intestinal obstruction (6).…”
Section: Introductionmentioning
confidence: 99%
“…11 Similar findings were also reported by Tsai et al, who suggested that routine closure of the mesenteric defect after laparoscopic right colectomy might not be beneficial. 12 In the case of laparoscopic left colectomy, Sereno-Trabado et al suggest that all mesenteric defects created during laparoscopic colorectal surgery should be closed given the high mortality rate associated with internal herniation (20%). 2,4…”
Section: Discussionmentioning
confidence: 99%
“…A 2010 cohort study of 530 patients undergoing laparoscopic right hemicolectomy found that four patients in the study developed small bowel obstruction due to the mesenteric defect, which the authors argued did not support closing mesenteric defects laparoscopically. 37 38 39 Other studies demonstrated that closure of mesenteric defects after partial colectomy may in fact be associated with increased risk of postoperative complications such as bowel obstruction. 40 Since the risk of internal hernia is very low after laparoscopic colon resection, 41 it is likely safe to assume that risk of internal hernia is low in open resection as well, thus perhaps not necessitating mesenteric window closure after open ileocolic anastomosis.…”
Section: Adjuncts To Anastomotic Constructionmentioning
confidence: 99%